Photocaged DNAzymes as a General Method for Sensing Metal Ions in Living Cells1. (14th October 2014) - Hwang, Kevin; Wu, Peiwen; Kim, Taejin; Lei, Lei; Tian, Shiliang; Wang, Yingxiao; Lu, Yi
Abstract DNAzymes, which are sequences of DNA with catalytic activity, have been demonstrated as a potential platform for sensing a wide range of metal ions. Despite their significant promise, cellular sensing using DNAzymes has however been difficult, mainly because of the "always‐on" mode of first‐generation DNAzyme sensors. To overcome this limitation, a photoactivatable (or photocaged) DNAzyme was designed and synthesized, and its application in sensing ZnII in living cells was demonstrated. In this design, the adenosine ribonucleotide at the scissile position of the 8–17 DNAzyme was replaced by 2′‐O‐nitrobenzyl adenosine, rendering the DNAzyme inactive and thus allowing its delivery into cells intact, protected from nonspecific degradation within cells. Irradiation at 365 nm restored DNAzyme activity, thus allowing the temporal control over the sensing activity of the DNAzyme for metal ions. The same strategy was also applied to the GR‐5 DNAzyme for the detection of PbII, thus demonstrating the possible scope of the method.